DETERMINANTS OF INTEGRATED REPORTING AND ITS IMPACT ON FIRM VALUE: LITERATURE REVIEW - Mulyadi, Humaira Dinda (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
Integrated reporting (IR) is the latest reporting that is important for use especially in Public Interest Entities (PIE). Unlike conventional reporting that only reports financial capital, integrated reporting includes other material information about manufacturing, intellectual, human, social and relational, and natural capital. Thus, the purpose of this study is to convey an understanding of IR and its contribution to the value of the company. Ultimately, this analysis includes useful recommendations for future IR research.